Comparison of Efficacy and Safety of Ferrous Bisglycinateand Ferrous Sulphate in Iron Deficiency Anemia (IDA) of Pregnant Patients: Comparative Analytical study - Fatima, Shafaq; Sohail, Irum; Sadiq, Hasina; Zaidi, Mahrukh Fatima; Riaz, Marium (Journal of Rawalpindi Medical College, 2025)
Objective: To compare oral ferrous bis-glycinate and ferrous sulfate as regards the mean change in haemoglobin, serum ferritin and tolerability in treating Iron Deficiency anaemia during pregnancy. Methods: This Experimental Study was carried out in the outdoor department of the Gynaecology and Obstetrics department of Kahuta Research Laboratories (KRL) hospital in Islamabad from 26th September 2022 to 26th March 2023. A total of 150 pregnant patients with iron deficiency anaemia were included in the study. Group I was for oral ferrous sulfate, Group II was for oral ferrous Bis-Glycinate. Hb level, serum ferritin and tolerability were noted from both groups after 8 weeks. Results: Mean Hb level was 9.760±0.63 g/dl in group I as compared to 10.853±0.81 g/dl in group II (p=0.000) after 8 weeks, and mean serum ferritin level was 23.640±1.14 ng/ml in group I as compared to 29.960±1.03 g/dl in group II (p=0.000) after 8 weeks. Conclusion: Our study has concluded that ferrous bis-glycinate has a superior efficacy in increasing HB level and serum ferritin, and also has better tolerability. Keywords: Pregnancy, Anaemia, Iron-Deficiency, Ferritins, Ferrous sulfate